Strategies for Vocational Rehabilitation of Persons with Special Needs in Nigeria - Bodang, Juliana Rotkanggmwa; Vandeh, C. M.; Ugo, E. (NIU Journal of Humanities, 2018)
Even though, disabled persons all over the world including Nigeria are gradually but steadily coming up by themselves as far as their economic and social emancipation in the society is concerned, particularly with the creation or advent of an increasing number of opportunities with which they can realize their potentials {such as exposure and access to education enlightenment, societal recognition, medical rehabilitation etc} the discovery is still made  that a very large percentage of the disabled persons population are losing out of this new consciousness due to their lack of access to vocational rehabilitation which for all practical purposes can be described as the viable alternative to the continued marginalization of the disabled. How this process is able to serve the employment interests of this group of people is what this paper shall endeavor to present.